ANALYSIS OF THE IMPACT OF THE USE OF HORMONAL BIRTH CONTROL (INJECTABLE) ON COUPLES OF CHILDBEARING AGE AT TECHNICAL IMPLEMENTATION UNIT (UPT) SIBULUE BONE REGENCY COMMUNITY HEALTH CENTER - Syahridayanti, Syahridayanti (Homes Journal: Hospital Management Studies Journal, 2022)
Background: The injectable method makes sex activities a dilemma in their use. This is because the long use of injectable contraceptives, which is more than 1 year, results in the accumulation of the hormone progesterone in the body so that the hormone estrogen is suppressed. This decrease in the hormone estrogen will affect the exit of the hormone testosterone. Whereas this hormone as a trigger for sexual arousal or libido. Objective: to analyze in depth regarding the impact of the use of hormonal (injectable) birth control on couple women of childbearing age. Method: this study uses qualitative methods with descriptive analysis with primary data collection techniques through indepth interviews. Results: The results of this study show that couples of childbearing age who use Hormonal birth control (injectable) there are some who experience libido disorders. However, among the acceptors who use hormonal birth control, both DMPA and cyclophemes that have more effect on decreasing libido function are DMPA injectable KB acceptors because they experience serious problems that require more treatment. Conclusion: that users of injectable birth control, both DMPA and cyclofem, both experience libido disorders.